2007
DOI: 10.1161/circulationaha.106.669101
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Use of Evidence-Based Pharmacotherapy in Heart Failure Is Associated With Improved Outcomes

Abstract: Background-Undertreatment with recommended pharmacotherapy is a common problem in heart failure and may influence prognosis. We studied initiation and persistence of evidence-based pharmacotherapy in 107 092 patients discharged after first hospitalization for heart failure in Denmark from 1995 to 2004. Methods and Results-Prescriptions of dispensed medication and mortality were identified by an individual-level linkage of nationwide registers. Inclusion was irrespective of left ventricular function. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 31 publications
15
133
4
5
Order By: Relevance
“…6,23 Smaller cohort studies in U.S. patients had similar findings regarding race, where minority or nonwhite race were significant predictors for nonadherence. 8,21 Other interesting findings from large cohort studies with follow-up ranging from 1 to 5 years in the United States, 6,23,32 Canada, 29 and European countries 22,27 identified those with more severe HF, 27 a greater a reduction in quality of life. [8][9][10][11][12][13][14] Furthermore, the Candesartan in Heart Failure Assessment of Reduction in Mortality and Morbidity (CHARM) study demonstrated that increased adherence to HF medications was associated with a 35% reduction in mortality (hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.57-0.75, P < 0.0001).…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 97%
See 1 more Smart Citation
“…6,23 Smaller cohort studies in U.S. patients had similar findings regarding race, where minority or nonwhite race were significant predictors for nonadherence. 8,21 Other interesting findings from large cohort studies with follow-up ranging from 1 to 5 years in the United States, 6,23,32 Canada, 29 and European countries 22,27 identified those with more severe HF, 27 a greater a reduction in quality of life. [8][9][10][11][12][13][14] Furthermore, the Candesartan in Heart Failure Assessment of Reduction in Mortality and Morbidity (CHARM) study demonstrated that increased adherence to HF medications was associated with a 35% reduction in mortality (hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.57-0.75, P < 0.0001).…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 97%
“…6,8,10,12,[21][22][23][24][25][26][27][28][29][30][31][32] Table 1 may assist the health care provider in recognizing predictors that may impact adherence to HF medications. Table 2 depicts a summary of the studies identifying predictors of decreased 6,8,10,[21][22][23][24][25][26]28,29,32 and increased 8,12,22,[26][27][28]30,31 HF medication adherence. Large, observational cohort studies extracting adherence and demographic data from health insurance claims databases or HF registries with 2 to 4 years of follow-up data from the United States found some similar significant predictors for nonadherence, including male gender or nonwhite race.…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 99%
“…Existing publication focus generally on single cohort of patients [8,16,[18][19][20][21]. We have chosen to compare different cohorts of hypertensive patients managed in the same geographical, clinical and organizational setting in order to have a comprehensive evaluation of the real world.…”
Section: Discussionmentioning
confidence: 99%
“…For other medications, patients were considered to be in treatment with a specific agent if they had claimed at least one prescription in the 6 months preceding echocardiography. To determine concomitant pharmacotherapy, the following agents (ATC codes) were identified: b-blockers (C07), statins (C10A), angiotensin-converting enzyme inhibitors and angiotensin-2 antagonists (C09), loop diuretics (C03C), thiazides (C03A), spironolactone (C03D), and calcium channel blockers (C08), as done previously (18).…”
Section: Identification Of Pharmacotherapymentioning
confidence: 99%